The Role of artificial intelligence in the Development of Innovative Drugs and Therapies for the Future of Health - Judijanto, Loso; Nurkhalika, Rachmi; Anurogo, Dito; Andari, Soetji; Muntasir, Muntasir (Journal of World Future Medicine, Health and Nursing, 2024)
The development of artificial intelligence (AI) technology has made significant contributions to the healthcare field, especially in the development of innovative drugs and therapies. The combination of computational sophistication and AI data analysis has enabled researchers to identify complex patterns in biomedical data, accelerate drug discovery time, and facilitate therapy personalization. This research aims to explore the important role of AI in drug development and innovative therapies to create a better future of healthcare. This involves an analysis of various AI methods and techniques used in drug development as well as the application of AI in personalized therapy for society. This study was conducted by conducting a literature review and analyzing the latest research and developments in the application of AI in drug and therapy development. The results showed that AI has opened new opportunities in drug development by accelerating the process of drug target identification, molecular simulation, and optimization of clinical trials. Meanwhile, in therapeutics, AI enables better personalization through analysis of patient clinical data and prediction of response to specific treatments. This opens up the potential for the development of more effective and targeted therapies. With the development of AI technology, the development of innovative drugs and therapies has become more efficient and effective. The application of AI in healthcare offers the potential to create a more personalized, precise, and comprehensive healthcare future. The collaboration between medical science and AI technology will lead to more innovative and affordable health solutions for the people. Thus, the role of AI in the development of innovative drugs and therapies is recognized as one of the key pillars in creating a better future of healthcare.